DIVERSITY OF BODY WEIGHT AND BODY SIZES SUPER VILLAGE CHICKEN - Jumardin, Jumardin; Nafiu, La Ode; Rahman, Rahman (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2020)
Super chicken is well known as one of the native chicken types which have high body weight which is compared with any other varieties from kampong chicken. But, information is engaged phenotype's characteristic quantitative chicken village super so circumscribed. Therefore in this research, Wight diversity warms up the body criteria for super evaluating village chickens to utilize 100 village super chickens. Weighing and measurement method is utilized for analyzing phenotypes (wight warms up body criteria) weight and measure all samples. Analyze at 4-time threads, Week-2 util 100 village chicken super, Week-4 util 100 heads, Week-6 util 78 heads, and Week 8 util 61 heads. The result of observational pointing out that wight average warms up is super age native chicken 8 weeks 792.30 ± 79.79 diversity coefficients (KK) 8.93. Meanwhile on a par-aged body criteria 8 wing range weeks 164.90 ± 12.73 KK 7.72, long hinder 141.06 ± 15.15 KK 10.74, long chest 72.16 ± 5.57 KK 7.72, long shank 77.25 ± 14.14 KK 18.30, long tibia 95.54 ± 7.05 KK 7.37, long femur 69.50 ± 5.39 KK 7.76, chest circular 20.64 ± 1, 57 KK 7.63, long claws 51.92 ± 4.29 KK 8.27, shank's diameter 11.01 ± 1.01 KK 9.16. Averagely wight warms up CHICKEN village super that maintained up to 8 uniform relative weeks with wight average warms up 792.30 ± 79.79 grams and diversity coefficient 8.93. While for criteria with diversity which is less than 15% or tending more uniform.